The Effectiveness of Butterfly Hug Therapy on Insomnia Among Undergraduate Students at Institut Teknologi Kesehatan Malang Widya Cipta Husada - Muhammad Taufiqul Akbar; Zilvi Fuadiyah Nur; Angriani Newa Lapur (Pro-Life, 2025)
Insomnia is a prevalent sleep disorder characterized by dissatisfaction with sleep quality and duration, leading to difficulty initiating sleep, frequent awakenings, early morning waking, and impaired daytime functioning. Non-pharmacological interventions, such as the butterfly hug technique, help improve sleep quality. The butterfly hug involves self-administered positive suggestions to promote relaxation and comfort. These studies examining the effectiveness of the butterfly hug among university students are still limited; therefore, based on the aforementioned background, the researcher is encouraged to conduct this study. This quasi-experimental study employed a nonequivalent control group design. A total of 54 final-year university students were recruited and divided into two groups: an intervention group and a control group. The intervention group received butterfly hug therapy, while the control group did not. The study was conducted over 14 consecutive nights. Insomnia levels were assessed using the KSPBJ-IRS questionnaire. Data normality was assessed using the Kolmogorov-Smirnov test, which revealed a non-normal distribution (p = 0.000 < 0.05). Therefore, the Mann-Whitney U test was used for hypothesis testing. The Mann-Whitney U test revealed a statistically significant difference between the intervention and control groups (p = 0.031, p < 0.05). This finding suggests that butterfly hug therapy was effective in reducing insomnia levels in the intervention group compared to the control group. Butterfly hug therapy has a significant effect on reducing insomnia among university students and may be considered a practical non-pharmacological intervention to improve sleep quality.